Evaluating the development and cutting capacity of a one-square computer numeric controlled milling machine - Ajayi, Oluwaseun Kayode; Oyeniran, Ayodele Temitope; Du, Shengzhi; Malomo, Babafemi Olamide; Alao, Kolawole Oluwaseun; Omotosho, Quadri Ayomide; Fawole, Marvellous Oluwadamilare; Lasaki, Ayomide Isaiah; Thompson, Godwin (Institute of Advanced Engineering and Science, 2025)
Traditional subtractive technology is rapidly losing significance with the advent of digital manufacturing technologies, which offer affordable machining with high accuracy and repeatability. Computer numeric controlled (CNC) machining has been around for a while; however, it has been costly to own one. Since the concept of CNC machining is now broadly understood and open-source software is available for control, designers can make use of available local materials to develop cheaper CNC machines. Hence, this presents the evaluation of the design and development of a one-square-meter CNC milling machine. The control was implemented on Arduino Uno, while open-source Universal G-code Sender (UGS) and G-code reference block library (GRBL) were used for the G-code generation and machine control, respectively. The built CNC was calibrated and tested on wood and plastic materials, and the resulting products were acceptable in accuracy up to ±0.02 mm in the first trial, but attained perfect accuracy by the third trial. Multiple tests repeatedly showed that accuracy was maintained. Since the machine is reconfigurable, future work entails automation and incorporating laser cutting capabilities into the machine.